Emoções no libelo introdutório de nulidade matrimonial - Rocha, Angélica Ferreira da Fonseca (2019)
This research questions the domains of language and law with the objective of characterizing the textual/discursive genre introductory libel for the annulment of marriage declaration in Canonical Law. The libel is a petition text, in which the newlyweds use textual sequences to argue the reasons that brought them to demand the annulment of the marriage. In this way, the study considers the lack of intelligibility of emotions as an argumentative element, inserted in a triad of Enunciative Responsibility, Discursive Representation, and Argumentative orientation. The study aims, thus, to investigate the relationship of emotions and argumentative orientation in 7 (seven) introductory libel for the annulment of marriage declaration. To do this, the research is grounded in a methodological approach from Textual Discourse Analysis (ADAM, 2011 [2008]); in Linguistic Enunciation studies of Rabatel (1997, 2007, 2008, 2009, 2010, 2013, 2016), and emotions from the rhetoric of passions (according to Aristotle), of Plantin (1995, 2008, 2010, 2011, 2012), Micheli (2008, 2010), Rodrigues and Passeggi (2015). It is characterized as a social, description and documental research, with a qualitative approach, interpretivist paradigm, and inductive method. The results show emotions of compassion, indignation, assurance, love, imprudence, fear, favor, shame, cholera, calm, contempt, and emulation. In virtue of this, the conclusions indicate that emotions rationalized in function of a seen action, understood through a perspective of argumentative moves, linked by a scale of intensity and a psychological place, configuring the point of view (POV) category given emotions.